Rhino poaching in Assam: challenges and opportunities - Martin, Esmond; Talukdar, Bibhab; Vigne, Lucy (Pachyderm, 2009)
Kaziranga National Park (NP) in Assam, India holds about 71% of the world’s wild population of the greater one-horned rhino. It was therefore a shock to conservationists when they learned that in 2007 about 20 animals were poached, a four-fold increase compared with the previous six years’ annual average. We analyse the reasons for this surge, which included the hasty choice in the change of top officials in Kaziranga, many vacancies in frontline staff who are needed to oversee the protection regime of Kaziranga day and night, and a shortage of funds for intelligence gathering. In Orang NP there was heavy poaching in 2008. New poachers entered the Park and the under-staffed frontline forest guards were not equipped to fight them. In contrast, there were no rhinos poached in Pabitora Wildlife Sanctuary (WLS) in either 2007 or 2008. This was because of a very close relationship between its staff and the local villagers. We recommend ways to improve the protection of Assam’s rhinos. These include how best to deter rhino poachers, especially with effective court cases, the urgent need to crack down on the rhino horn trade network that is based in Dimapur, Nagaland, and the importance of further strengthening the relationships between the Forest Department and the local people around rhino protected areas. Key words: Greater one-horned rhinos, Assam, park management, rhino poaching, rhino horn trade, Nagaland Le Parc National Kaziranga (PN) dans l’Assam, en Inde abrite approximativement 71% de la population mondiale du grand rhinocéros unicorne à l’état sauvage. C’était par conséquent un choc pour les défenseurs de l’environnement d’apprendre qu’environ 20 animaux ont été braconnés en 2007, une augmentation de quatre fois par rapport à la moyenne annuelle des six dernières années. Nous analysons les raisons de cette montée qui comprenait un choix hâtif dans le changement des cadres supérieurs dans Kaziranga, beaucoup de postes vacants parmi le personnel de terrain qu’il fallait pour superviser le régime de protection de Kaziranga jour et nuit, et une pénurie de fonds pour la collecte des informations. Dans le PN Orang il y avait beaucoup de braconnage en 2008. De nouveaux braconniers sont entrés dans le Parc et les gardes forestiers de terrain en sous effectif n’étaient pas équipés pour les combattre. Par contraste, il n’y avait pas de rhinocéros braconné dans le Sanctuaire de la Faune de Pabitora en 2007, ni en 2008, grâce aux liens très étroits entre son personnel et les villageois locaux. Nous recommandons des voies à suivre pour améliorer la protection des rhinocéros d’Assam. Celles-ci comprennent la façon dont on peut dissuader au mieux les braconniers de rhinocéros, surtout par des procès efficaces, le besoin urgent de réglementer le réseau du commerce de la corne de rhinocéros basé à Dimapur, Nagaland, et l’importance de renforcer les rapports entre le Département des Forêts et la population locale vivant à proximité des aires protégées du rhinocéros.